Characterization and application of immobilized Lactobacillus plantarum fiber powder as a probiotic starter culture for Thai-fermented pork - Pussadee Tangwatcharin; Supaluk Sorapukdee (Food Science of Animal Resources, 2026)
Characterization of immobilized Lactobacillus plantarum KL102 fiber powder and its application as a probiotic starter culture for probiotic Thai-fermented pork were evaluated. The influence of KL102 inoculum (free cells) and immobilized KL102 fiber powder additions on changes in microbiological and physicochemical qualities were estimated during 3 days of fermentation. For finished products, instrumental texture and color were collated. The results showed that the immobilized KL102 cells maintained their morphology and count within the banana peel dietary fiber after drying, with no significant difference observed. The addition of both forms of KL102 led to higher values of LAB, total acidity, and the proteolysis index, along with a lower pH and reduced levels of yeast, Enterobacteriaceae, Staphylococcus aureus, coliform, Escherichia coli, and lipid oxidation during the 3-day fermentation (p < 0.05). The released water content of samples to which immobilized KL102 fiber powder addition were lower than those of the others (p < 0.05). Mold and Salmonella spp. in all products during fermentation were not detected. The finished product with immobilized KL102 fiber powder exhibited lower hardness, gumminess and chewiness than the others (p < 0.05). The color of this batch was also less light and yellow than the others (p < 0.05). Finally, the addition of immobilized KL102 fiber powder produced improvement of product quality, and this powder proved to be a convenient probiotic starter culture with confirmed microbiological safety for Thai-fermented meat production.
Keywords: Probiotics and Fermented Foods; Meat and Animal Product Quality; Animal Nutrition and Physiology